Evaluation of ground source heat pump systems for residential buildings in warm Mediterranean regions: the example of Cyprus - Michopoulos, Apostolos; Voulgari, Vasiliki; Tsikaloudaki, Katerina; Zachariadis, Theodoros (My University, 2016)
This paper presents a feasibility analysis for the installation of ground source heat pump systems in Cyprus. Two reference buildings, a single- and a multi-family one, are designed and analyzed using the EnergyPlus software, in order to calculate their energy needs for heating and cooling for the climate conditions of Cyprus, one of the warmest areas in Southern Europe. These energy needs are assumed to be covered by the conventional heating and cooling systems that are most widely used in Cyprus or alternatively by a ground source heat pump system, which consists of a vertical ground heat exchanger and water-to-water heat pumps and is analyzed using an in-house developed and validated code. Primary energy consumption and the resulting CO2 emissions for both the conventional and the alternative systems are calculated and compared. Results show that the installation of the ground source heat pump system achieves in most cases substantial reductions in primary energy use for both types of buildings. As regards carbon emissions, the findings are less clear: Emissions of the geothermal system are higher than those of the conventional system for the single-family building but considerably lower for the multi-family one. From an economic perspective, the geothermal system compares favorably with the conventional systems in many cases, particularly for the multi-family building.
Keywords: CO2 emissions; Economic analysis; Energy analysis; Ground source heat pump; Residential buildings